Effect of Teriflunomide and Dimethyl Fumarate on Cortical Atrophy and Leptomeningeal Inflammation in Multiple Sclerosis: A Retrospective, Observational, Case-Control Pilot Study - Zivadinov, Robert (J Clin Med, 2019)
Background: Pathologic changes in cortical gray matter (GM) and leptomeninges contribute to disability worsening in patients with multiple sclerosis (MS), but there is little evidence whether disease-modifying treatments can slow down cortical pathology in MS. Objectives: To investigate the effect of teriflunomide (TFM) and dimethyl fumarate (DMF) in reducing cortical pathology, as determined by percentage cortical volume change (PCVC) and leptomeningeal contrast enhancement (LMCE) on MRI. Methods: This was a retrospective, single-center, observational study that selected 60 TFM- and 60 DMF-treated MS patients over 24 months. Results: TFM had a lower rate of PCVC compared to DMF over 24 months (−0.2% vs. −2.94%, p = 0.004). Similar results were observed for percentage GM volume change over 0–12 (p = 0.044) and 0–24 (−0.44% vs. −3.12%, p = 0.015) months. No significant differences were found between the TFM and DMF groups in the frequency and number of LMCE foci over the follow-up. TFM showed a numerically lower rate of whole brain atrophy over 24 months (p = 0.077), compared to DMF. No significant clinical or MRI lesion differences between TFM and DMF were detected over follow-up. Conclusions: These findings suggest that TFM has a superior effect on the preservation of cortical GM volume, compared to DMF.